2020
DOI: 10.1186/s12876-020-01206-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic healthcare records for colorectal cancer screening referral decisions and risk prediction model development

Abstract: Background The database used for the NHS Bowel Cancer Screening Programme (BCSP) derives participant information from primary care records. Combining predictors with FOBTs has shown to improve referral decisions and accuracy. The richer data available from GP databases could be used to complement screening referral decisions by identifying those at greatest risk of colorectal cancer. We determined the availability of data for key predictors and whether this information could be used to inform m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Considering the high morbidity and mortality of COVID-19 in the elderly, a possible protective effect through BCG in this group would invariably be of clinical significance. Nevertheless, ecological studies conducted so far have failed to establish this relationship [10]. It could be that these studies have all used a single indicator to depict immunity from BCG, which is commonly the population coverage of BCG vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high morbidity and mortality of COVID-19 in the elderly, a possible protective effect through BCG in this group would invariably be of clinical significance. Nevertheless, ecological studies conducted so far have failed to establish this relationship [10]. It could be that these studies have all used a single indicator to depict immunity from BCG, which is commonly the population coverage of BCG vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should also evaluate combinations of other risk factors, for example including FIT concentrations in previous screening rounds ( Chen et al, 2011 , Grobbee et al, 2017 ). Others have proposed to use data from medical records for screening, although privacy rights and regulations may form an obstacle ( Cooper et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that VH-based interference can effect users’ determinations outside of a laboratory environment. In [ 9 ], several potential predictors for CRC were recognized in a selected population of aged people using the interface among the screening database and primary care records. The authors observed that the considered predictors can be considered in a refined risk prediction model merging the newer quantitative FIT for bowel cancer screening.…”
Section: Related Workmentioning
confidence: 99%
“…It was revealed that VH-based interference can effect users' determinations outside of a laboratory environment. In [9], several potential predictors for CRC were recognized in a selected population of aged people using the interface among the screening database and primary care records.…”
Section: Related Workmentioning
confidence: 99%